Proses Morfologis Kolom Feature Maret 2023 di Media Hariansinggalang.co.id dan Waspada.co.id serta Rekomendasinya sebagai Bahan Ajar - Olivia, Feby Jolanda; Sugiarti, Dewi Herlina; Nurhasanah, Een (Jurnal Ilmiah Wahana Pendidikan, 2024)
Feature is an essay/article to provide information about a situation which contains facts and data obtained through a journalistic process which is conveyed in the mass media. Features published in online media have the use of language or word formation that is easy to understand so that readers can clearly receive the message delivered. Therefore, the use of language in the form of word formation in features can be studied in morphological processes. The purpose of this research is to describe the morphological processes in the March 2023 feature column in media harisinggalang.co.id and waspada.co.id. and make recommendations on the results of the analysis as teaching materials for news texts in junior high schools. This study uses the theory of morphological processes according to Rohmadi by applying a qualitative approach with descriptive methods. The research results from both media with a total of 10 news found 487 morphological processes in the form of 448 affixation data, 26 reduplication data, and 13 compounding data. Affixation or affixation processes on both media found 448 affixation data (246 prefix data, 4 infix data, 100 suffix data, and 98 confix data). The prefix meN- which functions to form verbs dominates the use of affixes in the media hariangsinggalang.co.id and waspada.co.id. Reduplication or repetition of words on both media found 26 reduplication data (13 reduplication data for all, 5 data for partial reduplication, and 8 data for reduplication with affixes). The compound words found in these two media are 12 data of endocentric compound words and 1 data of exocentric compound words. The results of the research conducted will be recommended as teaching materials in the form of digital handouts on news text material for junior high school level.